2016
DOI: 10.3329/sja.v13i2.26573
|View full text |Cite
|
Sign up to set email alerts
|

Production potential of newly released potato (Solanum tuberosum L.) cultivars under different nitrogen levels

Abstract: Field experiments were conducted during rabi seasons of 2011-12, 2012-13, 2013-14 and 2014-15 at C-unit research farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, Nadia, West Bengal, India to study the effects of different levels of nitrogen on the productivity of newly released potato (Solanum tuberosum L.) cultivars under lower Gangetic plains of West Bengal. The experiment was laid out in a factorial randomized block design with four replications having ten treatment combinations viz. two levels of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In addition, the discrepancies between N rates and observed yield may be related to the influence of other factors such as agronomics and producer management (LUZ; QUEIROZ; OLIVEIRA, 2014). Regarding management aspects, it was shown that some potato cultivars used for processing required about 150% more N and K than that of table potatoes (DAS et al, 2015). Similarly, we observed that the Atlantic-MG cultivar (used for processing) needed higher N inputs than that of Ágata-MG (by 23.7%) in order to achieve high yield; nonetheless, the Atlantic-MG cultivar showed lower yield.…”
Section: Yield Of Potato Tuberssupporting
confidence: 64%
“…In addition, the discrepancies between N rates and observed yield may be related to the influence of other factors such as agronomics and producer management (LUZ; QUEIROZ; OLIVEIRA, 2014). Regarding management aspects, it was shown that some potato cultivars used for processing required about 150% more N and K than that of table potatoes (DAS et al, 2015). Similarly, we observed that the Atlantic-MG cultivar (used for processing) needed higher N inputs than that of Ágata-MG (by 23.7%) in order to achieve high yield; nonetheless, the Atlantic-MG cultivar showed lower yield.…”
Section: Yield Of Potato Tuberssupporting
confidence: 64%
“…Plant height was 26.5% higher in plots treated with half FYM and half blended fertilizers as compared to the control. Das et al (2015) reported a similar response of potato height on a different variety. The significantly higher effects of combined organic and mineral fertilizers on yield components of potato might be attributed to their complementary effects, whereby the inorganic fertilizers enable the immediate availability of nutrients while the FYM supply nutrients slowly throughout the growing period and improve the soil properties such as soil porosity and reduced soil acidity (Fahmy et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…According to Banerjee et al [55], agronomic efciency was not afected by higher levels of fertilizers as compared to lower levels. Tis is due to the fact that the input-output relationship follows the law of diminishing returns when it comes to the relationship between N and yield, [64]. In this regard, the efciency of the variety to use the nutrient and the economical application of N fertilizers are critically important.…”
Section: Agronomic Efciency Of Nitrogen and Phosphorusmentioning
confidence: 99%